Peningkatan Hasil Belajar Siswa dengan Model Problem Based Learning pada Pembelajaran Tematik Terpadu - Ralita, Widia; Hamimah, Hamimah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
This research is motivated by the low student learning outcomes. The purpose of this study was to describe the improvement in student learning outcomes with the Problem Based Learning model in integrated thematic learning in fifth grade students of SDN 16 Koto Langang, South Coastal District. This type of research is classroom action research (PTK) using qualitative and quantitative approaches. The subjects of this study were teachers as observers, researchers as practitioners, and class V students as many as 28 people consisting of 16 male students and 12 female students. The study was conducted in two cycles. The results of the first cycle study on lesson plans averaged 76.79% (good), increasing in the second cycle to 92.85% (very good). The implementation of the first cycle on teacher activities averaged 80.35% (good), increasing in the second cycle to 96.42% (very good). The implementation of the first cycle on student activities averaged 76.79% (good), increasing in the second cycle to 96.42% (very good). Student learning outcomes in the first cycle averaged 62.83 (sufficient), increasing in the second cycle to 88.85 (good). Thus, it can be concluded that the Problem Based Learning (PBL) model can improve student learning outcomes in integrated thematic learning in elementary schools. Keywords : Learning outcomes, Problem Based Learning Models, Assessment